Development of a Model of Transformational Leadership Behavior and Ethical Leadership of Elementary School Principals in Creating Excellent Schools - Devi Ariani; Riswandi Riswandi; Dina Maulina (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to demonstrate elementary school principals' transformational and ethical leadership behavior. Method: This research is a type of research and development (R&D) research, and the development carried out refers to the Borg & Gall theory. The population of this study was school principals in Cluster 1 Diponegoro, Kasui District, Way Kanan Regency. The sample for this research was determined using a total sampling technique based on the research objectives: nine school principals in Gugus 1 Diponegoro. The data collection tool uses a valid and reliable questionnaire instrument. The data analysis technique uses a practicality test and questionnaire feasibility test with a calculated average value of 90 in the practical category. Results: The research results show that the model of transformational leadership behavior and ethical leadership of elementary school principals is practical. This is because the model of transformational leadership behavior and ethical leadership of school principals can significantly influence the quality and performance of teaching staff to create superior schools. Novelty: This research studies the topic further, showing that the model of transformational leadership behavior and ethical leadership of school principals greatly influence the quality and performance of teachers.